Salivary IgA and IgG antibodies to bullous pemphigoid 180 noncollagenous domain 16a as diagnostic biomarkers in mucous membrane pemphigoid3. (7th March 2016) - Ali, S.; Kelly, C.; Challacombe, S.J.; Donaldson, A.N.A.; Dart, J.K.G.; Gleeson, M.; ,; Setterfield, J.F.
Summary: Background: Mucous membrane pemphigoid (MMP) is an uncommon mucocutaneous immunobullous disorder. Use of saliva for diagnosis by enzyme‐linked immunosorbent assay (ELISA) using the noncollagenous (NC) domain 16a of bullous pemphigoid antigen II (BP180) is not well described. Objective: To establish whether whole or parotid saliva is a suitable alternative to serum for diagnosis of MMP. Methods: Precoated BP180‐NC16a ELISA plates were used to test serum, and whole and parotid saliva for IgG, IgA and secretory IgA antibodies. Patients with MMP ( n = 64) provided matched serum and whole saliva. In addition 18 of the MMP patients also provided matched parotid saliva. Healthy controls ( n = 50) provided matched serum and whole saliva and 6 of these additionally provided matched parotid saliva. An additional 16 disease controls provided matched serum, and whole and parotid saliva. Results: In whole saliva, IgG antibodies were detected in 11/64 (17%), IgA in 23/64 (36%) and a combined positivity in 29/64 (45%). In parotid saliva, IgA antibodies were found in 8/18 (44%). Serum IgG antibodies were detected in 27/64 (42%), serum IgA antibodies in 18/64 (28%) and a combined positivity in 33/64 (52%). Combined use of serum and saliva increased detection of specific antibodies by 30%. Control samples were all negative (positive predictive value of 100% for all tests). The negative predictive values were 62% for IgA saliva, 65% for IgG serum, 59% for IgA serum and 56% for IgG saliva. Conclusions: IgG and IgA antibodies may provide a suitable diagnostic marker in MMP. Assay of salivary IgA antibodies to NC16a offers a similar diagnostic predictive value to serum. Abstract : What's already known about this topic? The use of serum to test for specific IgG and IgA autoantibodies to epitopes on bullous pemphigoid antigen II (BP180; collagen XVII) by enzyme‐linked immunosorbent assay has been documented. Circulating autoantibodies may relate to disease activity and have been reported to be associated with a more severe clinical presentation in mucous membrane pemphigoid (MMP). What does this study add? The study demonstrates for the first time that saliva provides a practical alternative to serum in the diagnosis of MMP as IgG and IgA antibodies to BP180‐NC16a can be detected in saliva. The detection of secretory IgA antibodies is demonstrated for the first time and indicates local production of autoantibodies to the noncollagenous domain of BP180. This may help provide more insight into the pathogenesis of the disease. Linked Comment: Schmidt. Br J Dermatol 2016;174 : 956–957 Plain language summary available online